Impact of organization culture, workplace flexibility and compensation on Generation Z employees’ retention in banks of Bangladesh - Ria, Abida Parvin (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.